The political role of the press in Spanish transition to democracy, 1975-1978 - Montero, Mercedes; Rodríguez-Virgili , Jordi; García-Ortega, Carmela (Javnost-The Public, 2008)
This article analyses the behavior and attitude of the Spanish press at the beginning of the transition towards democracy (November 1975 – December 1978), during the most signifi cant political and institutional change. The role of the main newspapers is assessed from different perspectives, together with the reasons for the newspapers’ consensus on the basic issues that were in the public eye. Through examples from several papers, taken one by one and as a whole, we will explain the exceptional characteristics of this interesting relationship between politics and journalism, and include some exceptions such as the ultraright-wing press and the Basque nationalist sector.